2014
DOI: 10.1097/mlr.0000000000000225
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Providers and Administrators in the Veterans Health Administration Regarding Complementary and Alternative Medicine

Abstract: Background The integration of complementary and alternative medicine (CAM) therapies into a large organization such as the Veterans Health Administration (VHA) requires cultural change and deliberate planning to ensure feasibility and buy-in from staff and patients. Currently, there is limited knowledge of VHA patient care providers’ and administrators’ viewpoints regarding CAM therapies and their implementation. Objectives Our purpose was to qualitatively examine knowledge, attitudes, perceived value and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…Therapies most often mentioned included massage, meditation, acupuncture, and yoga. 8 All of these findings were confirmed and extended by the second multisite phase of the study. Although some sites are functioning at a much higher level and providing many more CIH therapies than others, respondents from even the highperforming sites cited challenges involving limited time, space, funding, and staff training.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Therapies most often mentioned included massage, meditation, acupuncture, and yoga. 8 All of these findings were confirmed and extended by the second multisite phase of the study. Although some sites are functioning at a much higher level and providing many more CIH therapies than others, respondents from even the highperforming sites cited challenges involving limited time, space, funding, and staff training.…”
Section: Discussionsupporting
confidence: 70%
“…However, they are consistent with the findings from the first portion of the study at the authors' local site. 8 In addition, the sites in the currently reported portion of the study represent a variety of geographic locations and approaches to the use of CIH therapies within the VA. While these preliminary findings cannot be generalized, they suggest that there are significant barriers to the implementation of CIH therapies in VA settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In one large-scale study (n = 401) conducted across five VA primary care clinics, 202 participants reported having sought massage for their chronic pain, and 387 participants (97%) reported willingness to try massage therapy; thus, massage was the most preferred of the complementary and alternative medicine modalities studied (massage therapy, chiropractic care, herbal medicines, and acupuncture). 18,19 A recent qualitative study of 28 patient care providers and administrators at a large VA facility rated massage as the top priority for promotion within the VA over 18 other modalities. 19 In this same study, although many participants saw lack of funding as a barrier to providing massage within the VA, others thought funding was available in response to a well-planned request.…”
Section: Secondary Outcome Measuresmentioning
confidence: 98%
“…18,19 A recent qualitative study of 28 patient care providers and administrators at a large VA facility rated massage as the top priority for promotion within the VA over 18 other modalities. 19 In this same study, although many participants saw lack of funding as a barrier to providing massage within the VA, others thought funding was available in response to a well-planned request.…”
Section: Secondary Outcome Measuresmentioning
confidence: 98%